Tracking Magmatic Hydrogen Sulfur Circulations Using Electrical Impedance: Complex Electrical Properties of Core Samples at the Krafla Volcano, Iceland. Issue 3 (9th March 2019) - Lévy, L.; Gibert, B.; Sigmundsson, F.; Deldicque, D.; Parat, F.; Hersir, G. P.
Abstract: Interaction of H 2 S escaping from magma and basaltic rocks leads to pyrite mineralization, witnessing active hydrothermal circulation. We study the possibility to track this process using geoelectrical methods. Complex conductivity spectra of 30 core samples from the Krafla volcano, Iceland, measured in the laboratory, indicate that pyrite can be discriminated from other minerals present in volcanic environments, such as iron oxides and clays. Joint evaluation of the maximum phase angle of electrical impedance and its real part at low frequency is required. The volume of metallic particles (pyrite or iron oxides) can be estimated from the maximum phase angle, but a decrease of the maximum phase angle with increased fluid conductivity or smectite volume is also observed and needs to be considered in the estimation. The laboratory observations can guide interpretation of field observations for estimation of pyrite volume in volcanic environments. Plain Language Summary: Hydrogen sulfur is a magmatic gas flowing under volcanoes. Its presence indicates ongoing geothermal activity, a clean and efficient source of energy. Upon exploitation of geothermal energy, this gas is extracted and needs to be reinjected in order to limit the environmental impacts. When hydrogen sulfur flows underground, a mineral forms by chemical transformation of the rock: pyrite. Therefore, pyrite indicates both where geothermal activity is and if hydrogen sulfur has been sequestrated upon reinjection. In order to track pyrite with geoelectrical methods, we study here the electrical signature of 30 natural samples from the Krafla volcano (Iceland): the capacity of the samples to both transfer and store electrical charges (conduction and polarization). Volcanic samples contain other minerals sensitive to electrical stimulation: iron oxides and smectite. Based on mineral quantification of pyrite, smectite, and iron oxides in the 30 samples, as well as on polarization and conduction measurements in a large range of frequency, we show that conduction at low frequency and maximum polarization are enough to discriminate pyrite from iron oxides. We also show that the volume of pyrite can be estimated from the maximum polarization but that an abundance of smectite tends to reduce this maximum, for a given pyrite volume. Key Points: Pyrite, iron oxides, smectite, and pore fluid conductivity influence the electrical impedance phase angle of volcanic rocks Volcanic rocks with high maximum phase angle contain pyrite if the real conductivity is also high For a given pyrite content, the maximum phase angle decreases with increasing smectite content